IN VITRO ANTIUROLITHIATIC ACTIVITY OF MACERATED AQUEOUS EXTRACT OF TERMINALIA BELERICA BY USING TURBIDITY METHOD - V., ANU; S., AKHILA; ANTONY, SNEHA (International Journal of Current Pharmaceutical Research, 2021)
Objective: To evaluate the anti-urolithiatic activity of macerated aqueous extract of Terminalia belerica by using turbidity method Method: The present study was used to study the inhibitory effect of the Terminalia belerica on urinary stone formation. The aim of study was to examine the In vitro antiurolithiatic activity of macerated aqueous extract of T.belerica was to estimate inhibitory activity of aqueous extract on the formation of urinary stone. Cystone was used as a positive control. Anti urolithiatic study was performed by turbidity method. Result: The percentage inhibition shown by aqueous extract at 20μg/ml was 60% and with almost constant inhibition at 100μg/ml and 200μg/ml ranging between 72% and 80%. The percentage inhibition showed by aqueous extract of Terminalia belerica has significant compared to standard drug. Conclusion: In future this drug can be performed in vitro and clinical study beneficial for people with avoiding adverse effect of modern medicinal drugs